Software Quality. The Future of Systems- and Software Development 8th International Conference, SWQD 2016, Vienna, Austria, January 18-21, 2016, Proceedings - Winkler, Dietmar; Biffl, Stefan; Bergsmann, Johannes (Lecture Notes in Business Information Processing, 2016)
This book constitutes the refereed proceedings of the scientific track of the 8th Software Quality Days Conference, SWQD 2016, held in Vienna, Austria, in January 2016. The SWQD conference offers a range of comprehensive and valuable information by presenting new ideas from the latest research papers, keynote speeches by renowned academics and industry leaders, professional lectures, exhibits, and tutorials. The five scientific full papers accepted for SWQD were each peer reviewed by three or more reviewers and selected out of 13 high-quality submissions. Further, nine short papers were also presented and are included in this book. In addition, one keynote paper by Scott Ambler and Mark Lines is also included.